THE MOVING PIONEERS IN AMERICA ON THE NOVELS BY JAMES FENIMORE COOPER - Sarlan Sarlan; Riyatno Riyatno (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
This research is an attempt to reveal the life of pioneers in America in Cooper’s novels “The Deerslayer”, “The Pathfinder”, “The Last of the Mohicans”, “The Pioneers” and “The Prairie”. There are two objectives of the research, namely the reasons why the pioneers move to the West and what things that they have to have in order to be successful in the West.Using literary sociology, the two objectives of the research are discussed in the five novels as the main sources and the criticisms and the social condition in America as the secondary sources.The result of the research shows that the pioneers in America have some reasons so that they move to the West.  They want to have wide land to settle.  Besides, they want to cultivate the land to fulfill their needs.  Other pioneers have to move to the West because they have to defend the British territory.  In order to be successful, the pioneers have to have the hard skills and soft skills.  They have to be able to hunt the wild animals, to use weapons to defend their properties and themselves.  They also have to have self reliance, hard work, spirit, and discipline as well as vigilance.